2D Electron Gas: Reversible Formation of 2D Electron Gas at the LaFeO3/SrTiO3 Interface via Control of Oxygen Vacancies (Adv. Mater. 10/2017). Issue 10 (March 2017) - Xu, Pengfa; Han, Wei; Rice, Philip M.; Jeong, Jaewoo; Samant, Mahesh G.; Mohseni, Katayoon; Meyerheim, Holger L.; Ostanin, Sergey; Maznichenko, Igor V.; Mertig, Ingrid; Gross, Eberhard K. U.; Ernst, Arthur; et al.
Abstract : In article number 1604447, Stuart Parkin and co‐workers demonstrate that the oxygen vacancy is a major contributor to the two‐dimensional electron gas formed at the interface between epitaxial LaFeO3 layers >3 unit cells thick and the surface of SrTiO3 single crystals. The ionic liquid gating geometry used to tune the interface conductivity by creation/removal of oxygen vacancies is shown here (Artwork: K. Roche).